2023
DOI: 10.1678/rheology.51.73
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Crispness of Porous Foods Using the Acoustic Emission Technique

Abstract: The acoustic emission (AE) technique was used to develop a method for the objective evaluation of the crispness of porous foods. The crispness of six types of commercial porous foods was changed by controlling their moisture contents at six levels by varying the humidity (i.e., dry, 22, 43, 56, 68, and 81 % relative humidity) of the storage environment at 25 °C. As the crispness of a sample with high water activity (a w ) was expected to deteriorate, the physicochemical, mechanical, and acoustic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The correlation and reproducibility of the E max (−0.167) and t (0.165) of Senbei are poor, which may be due to the uneven pore distribution of Senbei leading to the uneven peak value of cavity rupture vibration. Miura et al (2023) conducted acoustic and mechanical measurements on six commodities after they were treated with different hygroscopic conditions and also found that high‐precision acoustic characteristics can better characterize the brittleness of porous foods than mechanical characteristics. The energy release was concentrated in a shorter period, as shown in the Hilbert graph (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation and reproducibility of the E max (−0.167) and t (0.165) of Senbei are poor, which may be due to the uneven pore distribution of Senbei leading to the uneven peak value of cavity rupture vibration. Miura et al (2023) conducted acoustic and mechanical measurements on six commodities after they were treated with different hygroscopic conditions and also found that high‐precision acoustic characteristics can better characterize the brittleness of porous foods than mechanical characteristics. The energy release was concentrated in a shorter period, as shown in the Hilbert graph (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of baked goods, AE is specifically employed to evaluate textural attributes such as crispiness and crunchiness (Aboonajmi & Faridi, 2016). AE has been reported to measure the crispness of several baked products, including but not limited to cookies, biscuits, rice crackers, corn snacks, bread, extruded cereals, and snacks (Chanvrier et al, 2014;Hirte et al, 2010;Jakubczyk et al, 2017;Miura et al, 2023).…”
Section: Acoustic Emissionmentioning
confidence: 99%